Geographically structured genomic diversity of non-human primate-infecting Treponema pallidum subsp. pertenue. Issue 11 (30th November 2020) - Mubemba, Benjamin; Gogarten, Jan F.; Schuenemann, Verena J.; Düx, Ariane; Lang, Alexander; Nowak, Kathrin; Pléh, Kamilla; Reiter, Ella; Ulrich, Markus; Agbor, Anthony; Brazzola, Gregory; Deschner, Tobias; et al.
Abstract : Many non-human primate species in sub-Saharan Africa are infected with Treponema pallidum subsp. pertenue, the bacterium causing yaws in humans. In humans, yaws is often characterized by lesions of the extremities and face, while T. pallidum subsp. pallidum causes venereal syphilis and is typically characterized by primary lesions on the genital, anal or oral mucosae. It remains unclear whether other T. pallidum subspecies found in humans also occur in non-human primates and how the genomic diversity of non-human primate T. pallidum subsp. pertenue lineages is distributed across hosts and space. We observed orofacial and genital lesions in sooty mangabeys ( Cercocebus atys ) in Taï National Park, Côte d'Ivoire and collected swabs and biopsies from symptomatic animals. We also collected non-human primate bones from 8 species in Taï National Park and 16 species from 11 other sites across sub-Saharan Africa. Samples were screened for T. pallidum DNA using polymerase chain reactions (PCRs) and we used in-solution hybridization capture to sequence T. pallidum genomes. We generated three nearly complete T. pallidum genomes from biopsies and swabs and detected treponemal DNA in bones of six non-human primate species in five countries, allowing us to reconstruct three partial genomes. Phylogenomic analyses revealed that both orofacial and genital lesions in sooty mangabeys from Taï National Park were caused by T. pallidum subsp. pertenue . We showed that T. pallidum subsp. pertenue has infected non-human primates in Taï National Park for at least 28 years and has been present in two non-human primate species that had not been described as T. pallidum subsp. pertenue hosts in this ecosystem, western chimpanzees ( Pan troglodytes verus ) and western red colobus ( Piliocolobus badius ), complementing clinical evidence that started accumulating in Taï National Park in 2014. More broadly, simian T. pallidum subsp. pertenue strains did not form monophyletic clades based on host species or the symptoms caused, but rather clustered based on geography. Geographical clustering of T. pallidum subsp. pertenue genomes might be compatible with cross-species transmission of T. pallidum subsp. pertenue within ecosystems or environmental exposure, leading to the acquisition of closely related strains. Finally, we found no evidence for mutations that confer antimicrobial resistance.